PENYELUNDUPAN HUKUM OLEH BANK MELALUI KLAUSUL CROSS COLLATERAL DAN CROSS DEFAULT TERHADAP PERJANJIAN KREDIT - Ardini, Aida; Sinambela, Jamalum (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
In general, credit extended by banks to customer requires a guarantee (collateral) as Credit is carried out first by agreeing to the clauses in the credit agreement. One of these clauses is Cross Collateral which will have an impact on Cross Default if the debtor defaults. Cross Collateral and Cross Default clauses in credit agreements can potentially weaken and cause injustice to debtors. This esearch is a legal research thet uses statutory and conceptual approaches to discuss existing legal issues related to Cross Collateral and Cross Default clauses in credit agreements